2021
DOI: 10.1007/s00382-021-05840-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of environmental conditions on the significant difference in the super cyclone formation rate during the pre- and post-monsoon seasons over the Bay of Bengal

Abstract: Unlike other tropical ocean basins, the Bay of Bengal (BoB) has two tropical cyclone (TC) seasons: a pre-monsoon season (Pre-MS) and a post-monsoon season (Post-MS). More interestingly, during the period from 1981 to 2016, the global maximum and minimum formation rates of super cyclones (SCs, categories 4 and 5) occurred in the Pre-MS and Post-MS, respectively, in the BoB. Methods including Butterworth filter, box difference index analysis and quantitative diagnosis were utilized herein to detect what and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The relative contribution of each above‐mentioned physical process, could be measured by applying logarithms onto Equation (), following Li et al . (2020): logDGPI+1=falseitaliclogVsT1+false2×italiclogUyT2+false3×italiclogωT3+false2×italiclogζa12T4. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative contribution of each above‐mentioned physical process, could be measured by applying logarithms onto Equation (), following Li et al . (2020): logDGPI+1=falseitaliclogVsT1+false2×italiclogUyT2+false3×italiclogωT3+false2×italiclogζa12T4. …”
Section: Methodsmentioning
confidence: 99%
“…where V S =2:0 +0:1 × jvws 200 −vws 850 j represents the vertical wind shear (mÁs −1 ) between 200 and 850 hPa; U y =5:5 − ∂u 500 ∂y × 10 5 denotes the meridional gradient of zonal wind at 500 hPa; ω is the vertical velocity at 500 hPa; ζ a =5:5 +j ζ 850 + f ð Þ× 10 5 j represents the absolute vorticity at 850 hPa and f is the Coriolis parameter. The relative contribution of each above-mentioned physical process, could be measured by applying logarithms onto Equation (1), following Li et al (2020):…”
Section: Dynamic Genesis Potential Indexmentioning
confidence: 99%
“…On the other hand, the Southern and Eastern part of Kutubdia emerges to be gifted for wind electricity generation using large turbines where wind power density at the height of 50 m or higher is found to be above 200 W/m 2 annually over the year September 1996 to August 1997. It is found that at 30 m height, the coast side of Kutubdia should be sustainable for small turbines [27].…”
Section: Sunshinementioning
confidence: 99%
“…One peak is in the pre-monsoon transition period (April-May) and another peak is in the post-monsoon transition period (October-November) (Li et al 2013). In this paper, we use the term super cyclone ratio to refer to the ratio of the super cyclone frequency (with super cyclones defined as those having a maximum sustained windspeed ≥ 60 m s −1 , Li et al 2021) to the total TC frequency. Interestingly, the pre-monsoon and post-monsoon transition periods are very different in terms of TC intensification; during the premonsoon and post-monsoon periods, respectively, the BoB experiences the highest and lowest super cyclone ratio (Li et al 2021) in the world.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we use the term super cyclone ratio to refer to the ratio of the super cyclone frequency (with super cyclones defined as those having a maximum sustained windspeed ≥ 60 m s −1 , Li et al 2021) to the total TC frequency. Interestingly, the pre-monsoon and post-monsoon transition periods are very different in terms of TC intensification; during the premonsoon and post-monsoon periods, respectively, the BoB experiences the highest and lowest super cyclone ratio (Li et al 2021) in the world. However, both the annual cyclone frequency and average intensity are found to be higher in the post-monsoon (even though the super cyclone ratio is higher in pre-monsoon) than in the pre-monsoon season (Li et al 2013;Vissa et al 2013).…”
Section: Introductionmentioning
confidence: 99%